PERSEPSI SISWA PADA MATA PELAJARAN EKONOMI (STUDI KASUS PEMINATAN DI SMA NEGERI 1 PONTIANAK) - Silvia Oktadiani, Falcifera; ., Sri Buwono; Basri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research aims to determine the students' perceptions about economic subjects as cross-interest subjects in class X Mathematics 5 and 6 SMA Negeri 1 Pontianak. The method used is descriptive method to study the form of case studies. The data source of this study totaled 72 students. The results showed that the majority (38.89%) of students felt that the lack of economic subjects in accordance with the interests of students as subjects in class X interest cross Mathematics 5 and 6, the majority (80.55%) students can connect classroom content with the economic things that are experienced in everyday life, the majority (61.11%) students felt less need to explore the science of economics at further education and most (61.11%) students can understand the importance of ethics in entrepreneurship after studying economics. Â  Keywords: Perceptions of students, the economy and Specialisation Subjects Abstrak: Penelitian ini bertujuan untuk mengetahui persepsi siswa mengenai pelajaran ekonomi sebagai mata pelajaran lintas minat di kelas X MIPA 5 dan 6 SMA Negeri 1 Pontianak. Metode penelitian yang digunakan adalah metode deskriptif dengan bentuk penelitian studi kasus. Sumber data penelitian ini berjumlah 72 siswa. Hasil penelitian menunjukan bahwa sebagian besar (38,89%) siswa merasa bahwa pelajaran ekonomi kurang sesuai dengan minat siswa sebagai mata pelajaran lintas minat di kelas X MIPA 5 dan 6, sebagian besar (80,55%) siswa dapat menghubungkan isi pelajaran ekonomi dengan hal-hal yang dialami dalam kehidupan sehari-hari, sebagian besar (61,11%) siswa merasa kurang perlu mendalami ilmu ekonomi pada jenjang pendidikan selanjutnya dan sebagian besar (61,11%) siswa dapat memahami pentingnya etika dalam berwirausaha setelah mempelajari ekonomi. Kata Kunci: Persepsi siswa, Mata pelajaran ekonomi dan Peminatan